Radiological Study of the Effect of Omental Pedicel Flap on Fracture Healing in Unfixed Ribs in Dogs - Bader, O. A. (The Iraqi Journal of Veterinary Medicine, 2011)
This study was conducted to evaluate the effects of omental flap on healing of unfixed fractured ribs in dogs. Sixteen adult local breed dogs were used, which they were divided into two equal groups (Control and Treated group). The experimental animals were pre-medicated with atropine sulfate 0.04 mg/kg BW intramuscularly, and after 10 minute anesthetized with a mixture of Ketamine hydrochloride (15 mg/kg BW)and Xylazine hydrochloride (5 mg/kg BW) intramuscularly. In control group, the rib was fractured by wire saw and left unfixed then the muscles and skin was closed routinely. While in treated group, the rib was fractured by wire saw and a flap of omentum was put around the fractured rib, then muscles and skin were closed. Animals were observed clinically for one week and radiologically every week for three months. The radiological findings revealed that the healing process was faster in the treated group compared with the control group. The fracture line began to disappear in the eight and at the fourth weeks in the control and treated group respectively. The callus formation was large in size in control group compared with small dense callus in treated group. The remodeling process began in the fourth week in the treated group while at the eighth week in control group. These results indicated that the omental flap play an important role for enhancing healing and help to stabilize unfixed fractured ribs.